TEKNOLOGI PENYEDIAAN AIR BERSIH UNTUK WARGA TERDAMPAK GEMPA DI CUGENANG CIANJUR - Didit Sumardiyanto; Ricky Harianja; M.Fajri Hidayat; Sri Endah Susilowati; Herlina Muzanah Zain; Dinar Ayu Chandra Agustin (Universitas 17 Agustus 1945 Jakarta, 2023)
Geographical, demographic, sociological, meteorological and climatological dynamics in Indonesia not only make Indonesia rich in natural resources, but also make Indonesia prone to disasters (natural, non-natural and social). One of the geological disasters is an earthquake. This November an earthquake measuring 5.6 magnitude rocked Cianjur Regency. One of the very beautiful villages is Cibulakan Village. As a result of the earthquake, Cibulakan Village experienced physical damage, such as damage to residences and supporting facilities in the village. Apart from that, the loss of material, the earthquake also caused people to lack the availability of clean water. Through community service in providing clean water for residents, the Gemba in Cugenang Cianjur aims to provide clean water as well as overcome diseases caused by consumption of water that is not suitable for drinking. Fulfilling the need for clean water is also a form of continuing and maintaining people's lives. Clean water supply equipment in the form of an RO (reverse osmosis) machine can help the community in their daily life, in a sustainable manner and assist community activities both now and in the future.